Jak folk pamięta o folklorze? Uwikłania wyobraźni w pamięci i mitach o kulturze ludowej - Mirowski, Paweł (Humaniora. Czasopismo Internetowe, 2022)
This paper highlights the phenomenon of folk music in terms of a medium of cultural memory. The imaginaires about it are based on the Slavic and folk myth which shaped the forms of expressing folklore over the past two centuries. It is an attempt to switch the discussion from whether folk is able to have a positive influence in traditional folklore preservation, into the sphere of the identitiy issue. Folk music does not necessarily have to evoke the established Polish identity related to folk culture, but it gives an immediate sense of community, at supranational level, including the interslavic one.